The Influence of Safety Culture and Ship Engine Maintenance on Accident Prevention Which has Implications for Shipping Safety at PT Indo Container Lines - Silalahi, Tohonan; Erwin Manurung; Bambang Sumali; April Gunawan (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of safety culture and ship engine maintenance on accident prevention, which in turn affects maritime safety at PT Indo Container Lines. This research uses a quantitative approach with a cross-sectional research design. The sample used in this study consists of 107 crew members of PT Indo Container Lines, selected using the Slovin formula to determine a representative sample size. The data collected includes primary data obtained through questionnaires and interviews, as well as secondary data from the company's reports on safety and ship maintenance. The collected data was analyzed using SmartPLS software to test the relationships between the variables involved. The results of the study show that safety culture has a positive and significant impact on accident prevention, which in turn leads to improved maritime safety. These findings indicate that a strong safety culture, including awareness and safe behavior, plays a key role in reducing the risk of accidents during voyages. Additionally, ship engine maintenance was found to have a positive and significant impact on accident prevention, with well-maintained engines reducing the potential for technical failures that could jeopardize maritime safety. Accident prevention, driven by good engine maintenance and an applied safety culture, contributes to the overall enhancement of maritime safety. This study recommends that PT Indo Container Lines continue to strengthen the safety culture among its crew and enhance ship engine maintenance to support better maritime safety. By creating a safer work environment and ensuring that ships operate in optimal conditions, PT Indo Container Lines can reduce the risk of accidents and significantly improve maritime safety in the future